Peranan BUMDes Terhadap Pemenuhan Kebutuhan Sosial Warga Desa Marafala Kabupaten Nias Utara - Lase, Berkat Putra; Bawamenewi, Adrianus; Harefa, Anugerah Tatema; Lase, Berkat Persada (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine the role, obstacles and efforts of BUMDes in improving the fulfillment of the social needs of residents of Marafala Village, North Nias Regency. This research uses a descriptive approach with qualitative methods, with data collection techniques namely observation, interviews, documentation. The results of the research concluded that: First, the role of BUMDes in increasing the fulfillment of residents' social needs is still not fully implemented well because the type of BUMDes business is still constrained so that people feel dissatisfied with using BUMDes facilities. The two obstacles to BUMDes in increasing the fulfillment of residents' social needs are due to a shortage of goods needed by the community, and there are goods that are not suitable for use, the lack of public trust in BUMDes, and because BUMDes lacks business capital. Third, efforts to overcome BUMDes' obstacles in increasing the fulfillment of residents' social needs, namely the Village Government together with the BUMDes Director holding deliberations and reviewing the number of BUMDes goods.